2009
DOI: 10.1093/brain/awp112
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes of striatal and extrastriatal abnormalities in glutaric aciduria type I

Abstract: In glutaric aciduria type I, an autosomal recessive disease of mitochondrial lysine, hydroxylysine and tryptophan catabolism, striatal lesions are characteristically induced by acute encephalopathic crises during a finite period of brain development (age 3-36 months). The frequency of striatal injury is significantly less in patients diagnosed as asymptomatic newborns by newborn screening. Most previous studies have focused on the onset and mechanism of striatal injury, whereas little is known about neuroradio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
199
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 164 publications
(220 citation statements)
references
References 49 publications
15
199
1
5
Order By: Relevance
“…Category 2 patients had mainly motor regression due to incapacitating dystonia. A correlation between MRI findings and dystonia has been studied in detail earlier by Harting et al (2009) and Garbade et al (2014). These authors clearly showed that the severity of striatal lesions on MRI did correlate with the severity of the movement disorder.…”
Section: Clinical Spectrummentioning
confidence: 76%
See 1 more Smart Citation
“…Category 2 patients had mainly motor regression due to incapacitating dystonia. A correlation between MRI findings and dystonia has been studied in detail earlier by Harting et al (2009) and Garbade et al (2014). These authors clearly showed that the severity of striatal lesions on MRI did correlate with the severity of the movement disorder.…”
Section: Clinical Spectrummentioning
confidence: 76%
“…He has good compliance and is developmentally normal. All patients with or without crises had MRI abnormalities (Harting et al 2009). Eighty two percent of the patients (14/17) were already neurologically compromised (categories 2-4) at the time of presentation.…”
Section: Clinical Spectrummentioning
confidence: 99%
“…The late-onset case of GA-I presented here is remarkable for the following reasons: Few well-documented late-onset GA-I case reports have been published heretofore (B€ ahr et al 2002;Twomey et al 2003;Fernandez-Alvarez et al 2003;K€ ulkens et al 2005;Sonmez et al 2007;Harting et al 2009;Chen et al 2011). Our patient was asymptomatic at 16 years of age, apart from macrocephaly and mild psychomotor delay since infancy, and the diagnosis was made incidentally after a fainting episode during physical exercise without encephalopathy.…”
Section: Discussionmentioning
confidence: 81%
“…There have been scant reports in the medical literature, and in fact, some cases reported as "adult-onset GA-I" were simply childhood-onset GA-I diagnosed in adulthood (Prevett et al 1996;Corral I et al 2001;B€ ahr et al 2002;Twomey et al 2003;Fernandez-Alvarez et al 2003;K€ ulkens et al 2005;Sonmez et al 2007;Harting et al 2009;Chen J et al 2011). According to the few reports of truly adult-onset GA-I (onset at the age of 18 years or older), (1) the patients were paucisymptomatic or asymptomatic at the time of diagnosis, (2) the disease followed either an acute encephalopathic or a non-encephalopathic clinical course, and (3) in all cases supratentorial, diffuse, symmetric U-fiber-sparing leukoencephalopathy involving periventricular and deep white matter was seen in cranial MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because during brain development, energy requirements are high and in their most vulnerable phase (87,88), other brain-specific effects of 2HG could also be envisioned. D-2HG is taken up by astrocytes at high rates, potentially interfering with the uptake of ␣KG via the Na ϩ -dependent dicarboxylate transporter 3 (89,90).…”
Section: Discussionmentioning
confidence: 99%